Afectividad de los padres en el desarrollo cognitivo de los niños de 4 a 5 años en la Unidad Educativa Dr. Nicolas Coto Infante - Chiriguay Briones, Jennifer Leonela (2020)
The present study of the case study of affectivity of parents in the cognitive development of children from 4 to 5 years in the educational unit Dr. Nicolás Coto Infante of the canton Vinces, province of Los Ríos, seeks to broaden the knowledge of teachers about affectivity of parents and cognitive development in schoolchildren who are educated in this educational center. For this, the methods of observation and survey are applied to teachers and parents of material that makes it possible to demonstrate the need of students in cognitive development. The study was feasible as it was counted on the help of the authorities for its development. The results detected that 100% of teachers believe that the behavioral problems presented by children are sometimes due to the lack of affectivity of their parents. Likewise, the lack of concern of parents in the school performance of their children are factors that have an impact on learning. 39% of parents do not verbally express their love and love to their children. The formation of the personality through the teaching-learning process is intended to carry out early stimulation activities for three-year-old boys and girls, thus promoting affectivity and improving emotional skills, which must be worked in the classroom and the house, in this way generate security and confidence in children.